Assessing Active and Passive Glenohumeral Rotational Deficits in Professional Tennis Players: Use of Normative Values at 90° and 45° of Abduction to Make Decisions in Injury-Prevention Programs - Maite Terré; Juliette Tlaiye; Monica Solana-Tramunt (Sports)
(1) Background: Glenohumeral internal and external rotational range-of-movement deficits (GIRDs and GERDs) are some of the primary outcomes used to determine the risk of injury in overhead athletes, such as tennis players. Nevertheless, the current testing position does not consider the fact that most tennis actions are repeated at 45° of abduction, and actively. The aim of this study was to establish normative values of pathological GIRDs and GERDs in tennis players and to provide normative values for both the passive and active rotational range of motion of the glenohumeral joint at 90° and 45° of abduction. (2) Methods: Forty-three tennis players voluntarily participated in this study (19.1 ± 2.75 years). The dominant and non-dominant total glenohumeral rotational range of motion (TRROM), external rotation (ER), and internal rotation (IR) at 90° and 45° under active and passive conditions were evaluated. The GIRD and GERD were calculated in both positions and under both conditions. (3) Results: There were significant differences in all of the passive measurements between the 45° and 90° testing positions. The ER and TRROM at 90° and 45° showed significant differences under both passive and active conditions and on the dominant and non-dominant sides. Actively, there were no significant differences in the IR or TRROM for either the dominant or non-dominant side at 90° or 45°. (4) Conclusions: It is necessary to evaluate ER under the same conditions at 90° or 45°. Practitioners should consider assessing the ER for the angle at which most actions are repeated in tennis (45°) as a method to monitor GERDs. Evaluating GERDs in asymptomatic tennis players could help avoid future biomechanical and GIRD problems. Both GIRDs and GERDs should be considered as a percentage of the athlete’s own deficit in IR or ER, instead of referencing specific degrees that have been observed in baseball pitchers.